2020
DOI: 10.1101/2020.04.17.047225
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

MOSTWAS: Multi-Omic Strategies for Transcriptome-Wide Association Studies

Abstract: Traditional predictive models for transcriptome-wide association studies (TWAS) consider only single nucleotide polymorphisms (SNPs) local to genes of interest and perform parameter shrinkage with a regularization process. These approaches ignore the effect of distal-SNPs or possible effects underlying the SNP-gene association. Here, we outline multi-omic strategies for transcriptome imputation from germline genetics for testing gene-trait associations by prioritizing distal-SNPs to the gene of interest. In on… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
24
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 7 publications
(24 citation statements)
references
References 88 publications
(90 reference statements)
0
24
0
Order By: Relevance
“…MOSTWAS also allows for hypothesis generation for regulation of TWAS-detected genes, through distal mediating biomarkers, like transcription factors, miRNAs, or products downstream of CpG methylation islands 34 . Our computational results prioritized 89 GTAs with strong distal associations.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…MOSTWAS also allows for hypothesis generation for regulation of TWAS-detected genes, through distal mediating biomarkers, like transcription factors, miRNAs, or products downstream of CpG methylation islands 34 . Our computational results prioritized 89 GTAs with strong distal associations.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, of the 6 childhood BMI-associated genes identified by Peng et al, only 1 had a significant model in ELGAN and showed no association with the trait; there were no overlaps with childhood obesityassociated genes from Peng et al 10 . We hypothesize that minimal overlap with susceptibility genes identified by Peng et al is due to differing eQTL architectures in the datasets and different inclusion criteria for significant gene expression models 10,34,44,45 .…”
Section: Overall Associations and Permutation Testsmentioning
confidence: 95%
See 1 more Smart Citation
“…Recent work in transcriptome-wide association studies (TWAS) are a promising tool that aggregates genetics and transcriptomics to identify candidate trait-associated genes [110,111]. Incorporating information from regulatory biomarkers, like transcription factors and miRNAs, into TWAS increases study power to generate hypotheses about regulation [112,113]. Given our observations in this analysis and the number of the integrated molecular datasets, we believe that the ELGAN study can be used to train predictive models for placental transcriptomics from genetics, enriched for regulatory elements [113].…”
Section: Discussionmentioning
confidence: 99%
“…Incorporating information from regulatory biomarkers, like transcription factors and miRNAs, into TWAS increases study power to generate hypotheses about regulation [112,113]. Given our observations in this analysis and the number of the integrated molecular datasets, we believe that the ELGAN study can be used to train predictive models for placental transcriptomics from genetics, enriched for regulatory elements [113]. These transcriptomic models can then be applied to genome-wide association study cohorts to study the regulation of gene-trait associations in the placenta.…”
Section: Discussionmentioning
confidence: 99%